Do physicians have a duty to support secondary use of clinical data in biomedical research?: an inquiry into the professional ethics of physicians - Jungkunz, Martin; Köngeter, Anja; Winkler, Eva C.; Schickhardt, Christoph (The journal of law, medicine & ethics, 2024)
Secondary use of clinical data in research or learning activities (SeConts) has the potential to improve patient care and biomedical knowledge. Given this potential, the ethical question arises whether physicians have a professional duty to support SeConts. To investigate this question, we analyze prominent international declarations on physicians’ professional ethics to determine whether they include duties that can be considered as good reasons for a physicians’ professional duty to support SeConts. Next, we examine these documents to identify professional duties that might conflict with a potential duty of physicians to support SeConts.
Online veröffentlicht: 31. Mai 2024
Gesehen am 15.01.2025